The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/21582440211029941
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Predictors of Chinese College Students’ Entrepreneurial Intention

Abstract: The development and promotion of entrepreneurial behavior is an important ingredient in developing entrepreneurship ventures. This study examined the factors influencing college students’ intention to engage in entrepreneurial activities. Applying the Theory of Planned Behavior as the theoretical foundation the structural equation modeling technique through Smart PLS 3.0 was used to analyze the hypothesized relationship in this study. The results indicate that all the proposed research hypotheses were statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 105 publications
3
28
0
3
Order By: Relevance
“…The same finding was also found in a study conducted by Tsordia and Papadimitriou in business school students' entrepreneurial intentions in Greek [25]. The comparison study conducted by Mensah et al also shows that the three antecedents or factors positive effect on the formation of entrepreneurial intentions of students in China [26], so the hypothesis in this study is The results of the meta-analysis conducted by Zhao, Seibert and Lumpkin showed that, just like the career choice model, individual personality factors play a significant role important in forming one's intention to become an entrepreneur [27] [28]. Most research on EI often associates personality with focusing on the Big Five personalities [28][8].…”
Section: Theory Of Planned Behavior (Tpb)supporting
confidence: 77%
See 1 more Smart Citation
“…The same finding was also found in a study conducted by Tsordia and Papadimitriou in business school students' entrepreneurial intentions in Greek [25]. The comparison study conducted by Mensah et al also shows that the three antecedents or factors positive effect on the formation of entrepreneurial intentions of students in China [26], so the hypothesis in this study is The results of the meta-analysis conducted by Zhao, Seibert and Lumpkin showed that, just like the career choice model, individual personality factors play a significant role important in forming one's intention to become an entrepreneur [27] [28]. Most research on EI often associates personality with focusing on the Big Five personalities [28][8].…”
Section: Theory Of Planned Behavior (Tpb)supporting
confidence: 77%
“…The results of this study indicate that of the three antecendents or factors , the attitude variable and PBC In terms of attitude towards entrepreneurship, the role of the university as a source to gain knowledge related to entrepreneurship can help students to get the right mindset towards activities entrepreneurship which will ultimately improve their attitude towards entrepreneurship. Here, universities play a role in arming students with the right beliefs, processes, thinking, behaviour, and experience to launch a new business, which can positively impact their entrepreneurial intentions [26]. In addition, PBC or perception individual's confidence in himself to carry out entrepreneurial activities will also affect the formation of entrepreneurial intentions [13].…”
Section: Discussionmentioning
confidence: 99%
“…For college students, entrepreneurship is often motivated by personal pursuits, interest, and attitudes toward entrepreneurship and policy support for entrepreneurship is also an incentive for them to choose entrepreneurship as a career ( Mensah et al, 2021 ). However, the economic recession and recovery and the rise of some industries triggered by the unexpected event of COVID-19 have created more uncertainty about their career choices.…”
Section: Theoretical Foundations and Research Hypothesesmentioning
confidence: 99%
“…The theoretical model of planned behavior includes three elements: attitude, subjective norms, and perceived behavior control. Attitude refers to the entrepreneurs’ evaluation of this entrepreneurial behavior in entrepreneurship, which can be either positive or negative ( Mensah et al, 2021 ). Chen (2019) and Nithya and Lakshmi (2019) believed that subjective norms are the expectations of entrepreneurs who are influenced by the views of their parents, friends, and relatives.…”
Section: Methodsmentioning
confidence: 99%